Nitrogen isotope discrimination in open-pollinated and hybrid canola suggests indirect selection for enhanced ammonium utilization - Hu, Yi; Guy, Robert D.; Soolanayakanahally, Raju Y. (Frontiers in Plant Science, 2022)
Nitrogen isotope discrimination (15N) may have utility as an indicator of nitrogen use in plants. A simple 15N-based isotope mass balance (IMB) model has been proposed to provide estimates of efflux/influx (E/I) ratios across root plasma membranes, the proportion of inorganic nitrogen assimilation in roots (Proot) and translocation of inorganic nitrogen to shoots (Ti/Tt) under steady-state conditions. We used the IMB model to investigate whether direct selection for yield in canola (Brassica napus L.) has resulted in indirect selection in traits related to nitrogen use. We selected 23 canola lines developed from 1942 to 2017, including open-pollinated (OP) lines developed prior to 2005 as well as more recent commercial hybrids (CH), and in three separate experiments grew them under hydroponic conditions in a greenhouse with either 0.5 mM ammonium, 0.5 mM nitrate, or 5 mM nitrate. Across all lines, E/I, Proot and Ti/Tt averaged 0.090.03, 0.820.05 and 0.230.06 in the low nitrate experiment, and 0.310.06, 0.710.07 and 0.420.12 in the high nitrate experiment, respectively. In contrast, in the ammonium experiment average E/I was 0.400.05 while Ti/Tt averaged 0.070.04 and Proot averaged 0.970.02. Although there were few consistent differences between OP and CH under nitrate nutrition, commercial hybrids were collectively better able to utilize ammonium as their sole nitrogen source, demonstrating significantly greater overall biomass and a lower Proot and a higher Ti/Tt, suggesting a somewhat greater flux of ammonium to the shoot. Average root and whole-plant 15N were also slightly higher in CH lines, suggesting a small increase in E/I. An increased ability to tolerate and/or utilize ammonium in modern canola hybrids may have arisen under intensive mono-cropping.